Planning Budget For MSMEs Financial Performance - Sugianto; Gustini, Sri; Gilby Sapulette, Shella (Journal of Management, 2024)
This study seeks to investigate financial attitudes toward shopping interest. A case study of students from the Faculty of Engineering at Pasundan University in Bandung who utilize the Tokopedia application. The author employed a purposive sampling strategy for the sample in this study, which is classified as quantitative research. The sample size for this study was 88 people, and it focused on Tokopedia users who also attended the Faculty of Engineering at Pasundan University. The analytic approach is Multiple Linear Regression, and the research scale is a Likert scale. The findings of this study indicate that the Financial Literacy variable has a positive and significant effect on Shopping, whereas the Financial Technology variable has a positive and significant effect on Shopping Interest. Then, there is a favorable and considerable influence on Shopping Interest.